ROSTRUM-LENGTH-TOTAL-LENGTH RELATIONSHIP IN MACROBRACHWM 1DELLA AND M. SCABRfCULUM (DECAPODA, PALAEMONIDAE) - Jayachandran, K V; Balasubramanian, N K (Indian Journal of Fisheries, 2011)
A detailed statistical analysis of the rostrum length-total length relationship of two species of palaemonicl prawns Macrobrachium idella and M. scabriculum has been attempted. Two methods, analysis of covariance and body proportion index methods, were employed. The growth pattern of rostrum in relation to tola’ length of M. scabriculum was different in the two sexes whereas it was the same in the case of M. idella.